Functional implications of K63-linked ubiquitination in the iron deficiency response of Arabidopsis roots - Pan, I-Chun; Schmidt, Wolfgang (Frontiers in Plant Science, 2014)
Iron is an essential micronutrient that plays important roles as a redox cofactor in a variety of processes, many of which are related to DNA metabolism. The E2 ubiquitin conjugase UBC13, the only E2 protein that is capable of catalyzing the formation of noncanonical K63-linked ubiquitin chains, has been associated with the DNA damage tolerance pathway in eukaryotes, critical for maintenance of genome stability and integrity. We previously showed that UBC13 and an interacting E3 ubiquitin ligase, RGLG, affect the differentiation of root epidermal cells in Arabidopsis. When grown on iron-free media, Arabidopsis plants develops root hairs that are branched at their base, a response that has been interpreted as an adaption to reduced iron availability. Mutations in UBC13A abolished the branched root hair phenotype. Unexpectedly, mutations in RGLG genes caused constitutive root hair branching. Based on recent results that link endocytotic turnover of plasma membrane-bound PIN transporters to K63-linked ubiquitination, we reinterpreted our results in a context that classifies the root hair phenotype of iron-deficient plants as a consequence of altered auxin distribution. We show here that UBC13A/B and RGLG1/2 are involved in DNA damage repair and hypothesize that UBC13 protein becomes limited under iron-deficient conditions to prioritize DNA metabolism. The data suggest that genes involved in combating detrimental effects on genome stability may represent essential components in the plant’s stress response.